2021
DOI: 10.1371/journal.pone.0249309
|View full text |Cite
|
Sign up to set email alerts
|

The male bias of a generically-intended masculine pronoun: Evidence from eye-tracking and sentence evaluation

Abstract: Two experiments tested whether the Dutch possessive pronoun zijn ‘his’ gives rise to a gender inference and thus causes a male bias when used generically in sentences such as Everyone was putting on his shoes. Experiment 1 (N = 120, 48 male) was a conceptual replication of a previous eye-tracking study that had not found evidence of a male bias. The results of the current eye-tracking experiment showed the generically-intended masculine pronoun to trigger a gender inference and cause a male bias, but for male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…The category “native speaker” has been used to characterize a particular speaker population for many years (see Hopp, 2016 ; Azar et al, 2019 ; Ionin et al, 2021 ; Redl et al, 2021 as recent cases in point). What most researchers seem to agree on is that a native speaker is defined as a speaker who acquires their language naturalistically in early childhood ( Cook, 1999 ; Davies, 2004 , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The category “native speaker” has been used to characterize a particular speaker population for many years (see Hopp, 2016 ; Azar et al, 2019 ; Ionin et al, 2021 ; Redl et al, 2021 as recent cases in point). What most researchers seem to agree on is that a native speaker is defined as a speaker who acquires their language naturalistically in early childhood ( Cook, 1999 ; Davies, 2004 , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The sentence in (3) refers to a certain event in the past, hence it is episodic. Redl et al (2021) found male participants to show signs of a male bias (i.e., an increase in reading time when reference was made to women) in these episodic contexts. They concluded that the genericallyintended pronoun zijn 'his' can lead to a male bias as well.…”
Section: Een Minister Moet Zijn Verlies Kunnen Nemenmentioning
confidence: 85%
“…Thus, when a masculine generic role noun (e.g., German Studenten 'students (MASC)' in (1))though intended to refer to persons of all genders is used in episodic statements that denote specific events containing certain (groups of) individuals, readers often use the grammatical gender to infer the referents' supposed gender (e.g., for French and German see Garnham et al, 2012;Misersky et al, 2019). Redl, Frank, De Swart, and De Hoop (2021) found similar results for the processing of the Dutch masculine generic pronoun zijn 'his' in episodic contexts such as (3). They conducted an eye-tracking experiment in which they presented participants with sentences such as the following:…”
Section: Een Minister Moet Zijn Verlies Kunnen Nemenmentioning
confidence: 99%
See 1 more Smart Citation
“…More eye-tracking studies have been conducted investigating the influence in processing cost for both gender-neutral pronouns and the generic male pronoun. Irmen (2007) and Redl et al (2021) find male biases when using generic male pronouns in Dutch and generic role nouns in German. The authors of Sanford and Filik (2007) found a clear processing cost when using singular they in English, however their stimuli did not include any investigation of how (anti-)stereotypes influence this processing cost and is thus only in parts comparable to other studies.…”
Section: Related Workmentioning
confidence: 99%